Green Food Packaging in Supply Chain: Case Studies on Nestlé and Kraft Foods - Liu, Jiaxin (2014)
Problems concerning the environment are some of the most pressing issues our modern society faces, and such problems come in a variety of forms; climate change, deforestation, air pollution and water pollution. Packaging is one contributor to these environmental issues, as it involves results in waste, pollution and depletion of resources. As such, the food industry, an industry heavily reliant on packaging, has been forced to change its philosophy and become ‘green’. This paper will examine how companies are adopting green packaging policies and analyse their results & influence. One means of doing this will be through the use of case studies, and this study will look at Nestlé and Kraft Foods as examples. These case studies will be broken down into four main components; material, design, recycling and networks. These components will then be ranked according to seven scores; policy, data, packaging material, packaging design, networks and awards. As a result, Nestlé have better performance than Kraft Foods in general, although Kraft can be regarded as a good practice at some aspects such as YES pack programme. From LCA perspective, the outputs at each aspect are more than companies’ inputs. They have relevant packaging policies to put their plans into practice. Therefore, they have made good progress on packaging saving and recyclable material utilization. Moreover, the packaging design of their products has been improved successfully. By collecting, sorting and disposing of used packaging, the recycling system has good performance. All of these outcomes rely on their packaging network including information collection, employee training and cooperation with partners. Companies not only can improve their packaging system, even the supply chain, but also can reduce the negative environmental effects. Nestlé and Kraft can gain experience from other successful cases to perfect their operations at material, design, recycling and network stages. For environment, less packaging waste can lead to fewer pollutants environment and natural resources conservation. Moreover, they can achieve win-win situation with their partners and customers. Finally, they should keep green packaging as priority to achieve continuously improvement.